Morphological, growth, nodulation and membrane lipid peroxidation response of mani-mani (Arachis pintoi Krap. & Greg.) to elevated levels of cadmium and lead - Almenor, Grace A. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2007)
The response of mani-mani (Arachis pintoi Krap. & Greg) to increasing levels of Cd (0, 10, 15, 20 and 25 μM) and Pb (0, 10, 25, 50 and 100 μM) was evaluated in terms of the plant's morphology, growth and membrane lipid peroxidation. Mani-mani showed greater browning of leaves under Cd treatment compared with Pb. The highest decline in root and shoot dry weights, 0.1667g and 0.5667 g, respectively, was observed at 25 μM Cd. Lead treatment, however, did not significantly affect these characters. No significant difference was also noted in the root length of Cd-and Pb-treated plants. A significant reduction in nodule number was observed under Cd treatment, but the nodule size was not significantly affected by both metals. Mani-mani showed greater accumulation of Cd in both roots and shoots compared with the lead-treated plants at all levels. Root electrolyte leakage was highest at 20 (1.1343 mS/cm2) and 50 μM (0.8167 mS/cm2) for Cd and Pb, respectively, but declined at 25 μM (0.8217 mS/cm2) and 100 μM (0.4440 mS/cm2) for Cd and Pb, respectively. Mani-mani, in general, showed better tolerance to Pb than Cd.